Review on Major Insect Pests of Mango in Nepal: Impact, Identification, and Integrated Management Strategies - Niraula, Diwash; Dulal, Sandesh (Sustainability Science and Resources, 2025)
Mango(magnifera indica), called as king of fruits is widely cultivated in Nepal, where huge scales of production and sales are projected to reach approximately 300 millions in 2023.Althought having strong output,Mango industry faces several challenges from insect and pest which affect the quality and quantity in fruits yield.This articles examines the major pest affecting the mango crop in Nepal, including the mango hopper, mealybug, mango stem borer, mango fruit fly, and mango leaf webber. This paper discuss the nature of damage they causes, their biology and environmentally sustainable management practices.The promotion of integrated pest management practices is a crucial approach to mitigate the adverse affects of chemical pesticides, fostering environmental health and enhancing the economic benefits to Nepalese people. The reviews aim to provides insight into effective pest management solution, ensuring the sustainability of mango production in Nepal.